Changes in multiple breath washout measures after raised volume rapid thoracoabdominal compression maneuvers in infants. Issue 2 (18th September 2015) - Subbarao, Padmaja; Lu, Zihang; Kowalik, Krzysztof; Brown, Meghan; Balkovec, Susan; Gustafsson, Per; Lou, Wendy; Ratjen, Felix
SUMMARY: Multiple breath inert gas washout (MBW) measurements in infants are performed supine and often obtained under sedation and thus are combined with other lung function tests such as raised volume rapid thoracoabdominal compression (RVRTC). In this study, we sought to determine the effects of RVRTC maneuvers on MBW measures. Compared with tests performed prior to RVRTC, MBW measured after RVRTC was associated with a small reduction in functional residual capacity and a more pronounced decrease in cumulative expired volume in both healthy children and children with obstructive lung disease (cystic fibrosis or recurrent wheeze) indicating a more efficient washout after the raised volume maneuvers. Lung Clearance Index (LCI) decreased significantly in infants with respiratory disease (change in LCI of −0.24 units post RVRTC; standard error (SE) ± 0.07 units; P = 0.0004), but not in healthy infants (change in LCI of −0.08 units; SE ± 0.11 units; P = 0.44). As the RVRTC maneuver affects MBW measurements in infants, the timing of testing procedures needs to be standardized in longitudinal studies.Pediatr Pulmonol. 2016;51:183–188. © 2015 Wiley Periodicals, Inc.